Normative Guidelines for Rehabilitation Related Data Collection and Assessment for Tai Chi Chuan Movements - Chinese Association of Rehabilitation Medicine; Tao Jing; WU Jianhuang; JIN Rongjiang; TANG Qiang; ZHANG Yanxin; HUANG Jia; LIU Zhizhen; WU Jinsong; WANG Xiangbin; HOU Meijin; QIN Jiawei; et al. (康复学报)
Accumulative evidence has shown that Tai Chi Chuan has significant rehabilitative effects in the elderly and in those with chronic diseases. Based on different movement patterns, the individual stances of Tai Chi Chuan require different integrated abilities and also meet the needs of different rehabilitation goals. However, there is still lack of efficient means of collecting rehabilitation related data and accurate methods of assessing the quality of Tai Chi Chuan movements. Establishing specifications for data collection and assessment techniques for the Tai Chi Chuan movements can help to quantify the relevant research work. Uniform standards enable better integration and sharing of Tai Chi Chuan movements data. It can help to find the link between rehabilitation status and Tai Chi Chuan movements data more accurately, allowing better application of Tai Chi Chuan in rehabilitation training.Therefore, this standard regulates the terms and definitions of data collection for Tai Chi Chuan, techniques of data collection and assessment, facilities and equipment, personnel requirements, sites and environmental requirements,as well as assessment precautions for Tai Chi Chuan movements. This standard is applicable to rehabilitation related data collection and assessment of rehabilitation function for Tai Chi Chuan movements, with good feasibility, and safety.